12·13세기 웃음의 이론과 실천－웃음과 육체의 관련성을 중심으로 - 윤선자; Yun Sunja (史叢(사총), 0(115), 2025)
12·13세기 웃음이 해방되었다. 웃음의 이론과 실천은 육체와 밀접한 관련 속에서 발전했다. 고대 말과 중세 초의 신학자들은 웃음이 육체에서 나온다는 이유로 비난하고, 수도원은 웃음을 금지하는 계율을 만들었다. 이 시대 참된 웃음은 영적인 웃음, 내세의 웃음이었다. 12·13세기부터 웃음을 긍정적으로 인식하기 시작했는데, 그 이유는 신비한 체험이나 화체설 등에서 육체의 중요성이 커졌기 때문이다. 성 베르나르는 신비주의 이론을 기반으로 육체적 웃음, 현세의 웃음을 정당화하였고, 성 프란체스코는 이를 삶을 통해 실천하였다. 화체설과 위격적 결합 등 신학 논쟁의 연장선상에서 그리스도 웃음 논쟁이 발생했다. 성 토마스 아퀴나스는 이 모든 신학 논쟁을 종합하면서 웃음, 특히 재치를 기독교적 미덕으로 옹호했다. 하지만 신비주의와 스콜라주의의 웃음 인식은 매우 신중하고 제한적이었다. 그들은 육체, 특히 육체 하부와 관련된 웃음을 부정했고, 오히려 탄압했다. 12·13세기 민중의 ‘육체적 웃음’은 광인의 축제와 파블리오에서 잘 확인할 수 있다. 광인의 축제의 특징은 그로테스크한 뒤집기로서 정신과 영혼을 물질과 육체로 추락시켜, 그 부조화를 통해 웃음을 일으켰다. 파블리오는 수도사와 사제, 여성과 농민, 악당을 풍자하는, 웃음을 목적으로 하는 소극이다. 그 특징은 분뇨담과 외설, 폭력이다. 파블리오의 목적은 도덕적 교훈과 웃음이다. 중세 기독교적 인간론을 배경으로 비유사성의 영역에서 인간의 육체성과 타락을 보여줌으로써 도덕적 각성과 세속적 지혜를 전달하고자 했다. 하지만 이런 도덕성은 웃음이라는 본질적 목적 앞에서 폐기된다. 파블리오는(광인의 축제도 마찬가지인데) 육체성과 모호성을 특징으로 하는 카니발적이고 그로테스크한 세계를 펼쳐 보이고, 거기서 모든 것을 뒤섞어 웃음의 세계를 만든다. 그 세계는 ‘신이 사라진 보편적 광기의 세계, 몽드 베스투르네’이다. 거기엔 선악의 도덕적 이분법이 없으며, 오로지 생육하는 육체, 삶과 생명에 대한 긍정만이 존재한다. 민중의 웃음은 교회의 영적인 웃음에 저항하고 도덕적 교훈을 전달하는 육체적 웃음이었을 뿐만 아니라, 영혼-육체의 이분법을 넘어서 삶과 생명 그 자체를 찬양한 절대적 웃음이다. In the 12 th and 13 th centuries, laughter was liberated. The theory and practice of laughter developed in close connection with the body. Late ancient and early medieval, theologians condemned laughter on the grounds that it came from the body, and monasteries created rules forbidding laughter. The true laughter of this age was spiritual laughter, the laughter of the Paradise. From the 12 th and 13 th centuries, laughter began to be perceived positively, as the importance of the body grew in mystical experiences and Transubstantiation. St. Bernard justified physical laughter and worldly laughter, based on mystical theories, and St. Francis put this into practice in his life. The controversy over Christ's laughter arose as an extension of the theological debates over Transubstantiation and the Hypostatic Union. St. Thomas Aquinas synthesized all these theological debates and defended laughter, especially eutrapelie, as a Christian virtue. But the perception of laughter in mysticism and scholasticism was very cautious and limited. They denied, and rather repressed, laughter associated with the body, especially the lower parts of the body. The ‘physical(carnal) laughter’ of the people in the 12 th and 13 th centuries can be clearly seen in the festival of the fools and pabliaux. The characteristic of the festival of the fools was a grotesque reversal, a rabaissement of mind and soul into material and body, and arousing laughter through this dissonance. Fabliau is a farce that specializes in laughter, satirizing monks and priests, women and peasants, and villains. Its features include scatology, obscenity, and violence. The purpose of the fabliau is moral lessons and laughter. It aims to convey moral lessons and worldly wisdom by showing physical corruption in the realm of dissimilarity against the backdrop of medieval Christian anthropology. But this morality is discarded in the essential purpose of laughter. Fabliau (as well as the festival of the fools) makes a carnivalesque and grotesque world characterized by physicality and ambiguity, and mixes everything up to create a world of laughter. That world is ‘Monde Bestournee, the world of universal folly where God has disappeared.’ There is no moral dichotomy of good and evil, only the affirmation of the growing body, life itself. The laughter of the people was not only a physical laughter that resisted the spiritual laughter of the church and conveyed moral lessons, but it was also ‘an absolute laughter’ that praised life itself, transcending the duality of soul and body.